Peran Penting Kekuatan Tawar dan Kapasitas Penyerapan dalam Joint Venture: Kajian Manajemen Puncak Industri Otomotif Indonesia - Jepang - Sudhartio, Lily; Wahyuni, Sari (Universitas Prasetiya Mulya, 2010)
This research examined the influence of bargaining power and absorptive capacity on value appropriation, appropriated relational rent and inbound spillover rent in IJV. The main objective of this study is to find out variable in appropriated relational rent and inbound spillover rent which can be appopiate by local partner.This research is applying both qualitative (explorative) and quantitative research. The explorative study was conducted by indepth interview with Board of Director (BOD0 and General Manager of local partner in automotive industry. We use descriptive analysis and Structural Equation Model (SEM) in our qualitative research. The result of this study shows that value appropriation both appropriated relational rent and inbound spillover rent could only be achieved by local partners through the improvement of absorptive capacity. On the other hand, bargaining power which is normally held via control has no significant relation with appropriate performance.